Electrochromic evaluation of airbrushed water-dispersible W18O49 nanorods obtained by microwave-assisted synthesis. (5th March 2021) - Scarfiello, Riccardo; Prontera, Carmela Tania; Pugliese, Marco; Bianco, Giuseppe Valerio; Bruno, Giovanni; Nobile, Concetta; Carallo, Sonia; Fiore, Angela; Sibillano, Teresa; Giannini, Cinzia; Giannuzzi, Roberto; Carbone, Luigi; et al.
Abstract: Motivated by the technological relevance of tungsten oxide nanostructures as valuable materials for energy saving technology, electrochemical and electrochromic characteristics of greener processed nanostructured W18 O49 -based electrodes are discussed in this work. For the purpose, microwave-assisted water-dispersible W18 O49 nanorods have been synthesized and processed into nanostructured electrodes. An airbrushing technique has been adopted as a cost-effective large-area scalable methodology to deposit the W18 O49 nanorods onto conductive glass. This approach preserves the morphological and crystallographic habit of native nanorods and allows highly homogeneous transparent coating where good electronic coupling between nanowires is ensured by a mild thermal treatment (250 °C, 30 min). Morphological and structural characteristics of active material were investigated from the synthesis to the nanocrystal deposition process by transmission and scanning electron microscopy, x-ray diffraction, atomic force microscopy and Raman spectroscopy. The as-obtained nanostructured film exhibited good reversible electrochemical features through several intercalation–deintercalation cycles. The electrochromic properties were evaluated on the basis of spectro-electrochemical measurements and showed significant optical contrast in the near-infrared region and high coloration efficiency at 550 nm.